Associations of stream health with altered flow and water temperature in the Sierra Nevada, California. Issue 6 (21st December 2015) - Carlisle, Daren M.; Nelson, S. Mark; May, Jason
Abstract: Alteration of streamflow and thermal conditions may adversely affect lotic invertebrate communities, but few studies have assessed these phenomena using indicators that control for the potentially confounding influence of natural variability. We designed a study to assess how flow and thermal alteration influence stream health – as indicated by the condition of invertebrate communities. We studied thirty streams in the Sierra Nevada, California, that span a wide range of hydrologic modification due to storage reservoirs and hydroelectric diversions. Daily water temperature and streamflows were monitored, and basic chemistry and habitat conditions were characterized when invertebrate communities were sampled. Streamflow alteration, thermal alteration, and invertebrate condition were quantified by predicting site‐specific natural expectations using statistical models developed using data from regional reference sites. Monthly flows were typically depleted (relative to natural expectations) during fall, winter, and spring. Most hydrologically altered sites experienced cooled thermal conditions in summer, with mean daily temperatures as much 12 °C below natural expectations. The most influential predictor of invertebrate community condition was the degree of alteration of March flows, which suggests that there are key interactions between hydrological and biological processes during this month in Sierra Nevada streams. Thermal alteration was also an important predictor – particularly at sites with the most severe hydrological alteration. Copyright © 2015 John Wiley & Sons, Ltd.